Fabrication of electrically conductive microparts by constructing carbon black-rich network under high shear conditions in microinjection molding - Lei, Xue; Gong, Xiaoxi; Li, Jixiang; Shi, You; Liang, Mei; Zou, Huawei; Zhou, Shengtai (Frontiers in Materials, 2024)
Microinjection molding (μIM) is an important technique to fabricate microparts for applications in the fields of automotive and microelectromechanical systems. However, the prevailing high shear conditions in μIM is unfavorable for constructing intact electrically conductive networks because the added fillers tend to be preferentially aligned along the melt flow direction. In this work, a series of polypropylene/polyamide 6/carbon black (PP/PA6/CB) composites with a selective localization of CB in the PA6 phase were used as the model system to prepare electrically conductive microparts. The prevailing high shearing and extensional flow effects in μIM were utilized to deform CB-rich phase with an aim to in situ construct electrically conductive network, thereby improving the electrical conductivity (σ) of subsequent moldings. The results indicated that a higher σ was achieved for PP/PA6/CB microparts when compared with their PP/CB and PA6/CB counterparts, at a lower filler content (<10 wt%). The influence of blending sequence of various components (i.e., PP, PA6, and CB) and annealing treatment on the σ of microparts was also studied. This work provided an approach to the design and preparation of electrically conductive microparts that can be potentially used in high-tech sectors.